Long Term Effect of Fertilizers on Availability of Micronutrients in Soil under Wheat Rice Intensive Cropping System: Impact of Fertilizer Application on Micronutrient Availability in Wheat-Rice Cropping System (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It has observed that the application of fertilizers, in general, depleted availability of Zn in soil on comparing with the control. Nitrogen application alone or combination with phosphorus showed decreasing trend of Zn. Maximum reduction was recorded under NPK treatment. The availability of Zn decreased by 23 per cent with cropping and it was maximum after wheat harvest than that after rice harvest. The availability of Fe, over seven seasons increased to the extent of 15-20 percent over control. However, the highest availability of Fe in soil was found consequent upon application of nitrogen alone, followed by combined application of nitrogen and phosphorus. The availability of Mn increased significantly over control and also over nitrogen alone. On an average, the availability of Mn increased 3, 5 and 10 per cent with N, NP and NPK fertilizer application. On the basis of relative values, available Cu was in the range of 91-96 per cent after rice and 83-98 per cent after wheat, when initial value of 1.74 ppm Cu at the start was considered as 100. The overall reduction in Cu content was found to be 16 per cent after harvest of wheat.Intensive use of fertilizers, intensive cropping and high yielding seeds have no doubt brightened the hopes of huminity for successfully meeting the challenge of food shortage, but it has also brought into the sharp focus numerous problem of soil fertility, fertilizer, soil and water management. Universal deficiency of nitrogen and serious deficiency of phosphorus and potassium and increasing deficiency of micro nutrients particularly Zn, Fe and Mn could be well understood under soil fertility problems, in modern agriculture. The continuous application of fertilizers N, P and K could help to improve such nutrients deficiencies due to imbalanced application of fertilizers under intensive farming systems in case of micronutrients.